Research on the Application of Blockchain Technology in Financial Risk Management - Li, Yuxuan (Journal of Global Economy, Business and Finance, 2024)
This paper explores the application of blockchain technology in financial risk management. By analyzing foundational blockchain concepts such as public and private chains, smart contracts, and consensus mechanisms, the paper first illustrates how blockchain is transforming financial risk management practices. Additionally, it highlights challenges related to scalability, interoperability, and regulatory/legal barriers. Finally, the paper discusses innovative opportunities that blockchain presents for financial risk management, aiming to provide financial institutions with new strategies and insights to tackle modern financial challenges.